The deadly gap: Understanding suicide among veterans transitioning out of the military. (June 2021) - Sokol, Yosef; Gromatsky, Molly; Edwards, Emily R.; Greene, Ashley L.; Geraci, Joseph C.; Harris, Rachel E.; Goodman, Marianne
Highlights: Transitioning Veterans are at higher risk for suicide compared to other Veterans. This narrative review uses the 3ST framework to clarify their risk. Prevalent mental, physical, social/reintegration difficulties may increase their risk. Greater suicide capability from military service may also increase risk. Barriers to psychiatric services during transition produce a "deadly gap" in care. Abstract: In the period following separation from the military, service members face the challenge of transitioning to a post-military civilian life. Some evidence suggests these transitioning Veterans are at higher risk for suicide compared with both the broader Veteran population and the United States public, yet they often do not receive adequate support and resources. In this review, we use the Three-Step Theory of suicide to outline characteristics of transitioning Veterans and the transition process that may affect suicide risk. We then highlight relevant services available to this specific subgroup of Veterans and make recommendations that address barriers to care. Cumulatively, this literature suggests transitioning Veterans fall within a "deadly gap" between the end of their military service and transition into civilian life. This "deadly gap" consists of limited psychiatric services and increased suicide risk factors which together may explain the increase in suicide during this transition period.